1997
DOI: 10.1097/00005392-199709000-00134
|View full text |Cite
|
Sign up to set email alerts
|

Critical Analysis of the Clinical Presentation of Acute Scrotum

Abstract: We believe that any boy 11 years old or older with scrotal pain less than 12 hours in duration that is associated with nausea or vomiting should be considered to have torsion of the spermatic cord. In this day of cost-effective medical management it is not necessary to perform imaging in this subset of boys before surgical exploration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Duration of symptoms before surgery is an important predictor of outcome in TT ( 14 ). Jefferson et al ( 15 ) reported that no testicle with a history longer than 12 hours could be salvaged. Other researchers ( 11 ) observed testicular necrosis, even atrophy after orchidopexy in patients with the history shorter than 10 hour.…”
Section: Discussionmentioning
confidence: 99%
“…Duration of symptoms before surgery is an important predictor of outcome in TT ( 14 ). Jefferson et al ( 15 ) reported that no testicle with a history longer than 12 hours could be salvaged. Other researchers ( 11 ) observed testicular necrosis, even atrophy after orchidopexy in patients with the history shorter than 10 hour.…”
Section: Discussionmentioning
confidence: 99%
“…Testicular torsion instances that are clinically evident or those identified by colour duplex ultrasonography should always be handled urgently [ 16 ]. It is recommended to do scrotal exploration, bilateral testicular fixation, and detorsion of the affected side [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…and that study quoted a salvage rate of 61%. [ 24 ] Barada et al . from new York report a delay of 20 h for those below 18 years of age making them a target population for education regarding testicular health.…”
Section: Discussionmentioning
confidence: 99%